Kurikulum Kearifan Lokal Bali Berbasis Heutagogy di Sekolah Dasar - Ayu Sukma Trisna; Dinn Wahyudin; Rusman Rusman; Cepi Riyana; Andria Pragholapati (Journal of Elementary School (JOES), 2022)
This study focuses on dissecting the heutagogy-based local wisdom curriculum as a strategy for optimizing primary school student learning. The study method uses bibliographic research by prioritizing the integrity and accuracy of sources, relationships, meaning relations, and conformity with the focus of the study. Based on the results of the study, it can be concluded as follows: (1) The local wisdom curriculum is a curriculum model that elaborates and actualizes a set of noble values ​​that are embraced or have become the belief of a society, which is adapted to the characteristics of the educational goals that have been previously set. , (2) Heutagogy is a learning approach that optimally provides opportunities for students to make choices freely about the material to be studied and how to learn it, (3) heutagogy is not only oriented to efforts to master a certain competence, but also to capacity building. and the capability of students' competencies, including elaborating the local values ​​of the community, so that this makes the learning outcomes of students better and more meaningful.